Structural Insights on Tiny Peptide Nucleic Acid (PNA) Analogues of miRNA-34a: An in silico and Experimental Integrated Approach - Moccia, Maria; Mercurio, Flavia Anna; Langella, Emma; Piacenti, Valerio; Leone, Marilisa; Adamo, Mauro F. A.; Saviano, Michele (Frontiers in Chemistry, 2020)
In the present work, structural features of the interaction between peptide nucleic acid (PNA)-based analogs of the tumor-suppressor microRNA-34a with both its binding sites on MYCN mRNA were investigated. In particular, the region from base 1 to 8 (“seed” region) of miR-34a was reproduced in the form of an 8-mer PNA fragment (tiny PNA), and binding to target 3'UTR MYCN mRNA, was studied by a seldom reported and detailed NMR characterization, providing evidence for the formation of anti-parallel duplexes with a well-organized structural core. The formation of PNA-3'UTR duplexes was also confirmed by Circular Dichroism, and their melting curves were measured by UV spectroscopy. Nevertheless, this study offered a valuable comparison between molecular dynamics predictions and experimental evidence, which showed great correlation. Preliminary uptake assays were carried out in Neuroblastoma Kelly cells, using short peptide conjugates as carriers and FITC fluorescent tag for subcellular localization. Moderate internalization was observed without the use of transfecting agents. The reported results corroborate the interest toward the design and development of chimeric PNA/RNA sequences as effective RNA-targeting agents.